Four Chinese ELLs : their school experiences and journeys in pursuing the American dream - Li, Nan, 1960-; Meng, Michael, 1987- (Emerald Publishing Limited : IAP/Information Age Publishing Inc., 2020)
"First, this book can be marketed through the TESOL organizations. The TESOL has one of the largest memberships with over 12,000 members representing 156 countries (TESOL Brochure, 2017). Beyond TESOL International, many regional and local TESOL organizations are affiliated with TESOL. For example, SETESOL stands for the Southeastern Regional TESOL and the Carolina TESOL is in South/North Carolina. Marketing can be done through the websites of these organizations or at their annual conferences. We have the ESOL coordinators in several school districts who are closely related to the TESOL International and the local TESOL to help with the book marketing. Second, this book can be marketed through other professional conferences. More national, international, regional and local conferences have begun to pay attention to teaching ELLs. For example, the AERA annual meetings have SIG Divisions on educating ELLs. The ATE and NAME Annual Conferences have also added the topics related to teaching ELLs in recent years. This book can be marketed at these annual meetings/conferences through their book exhibit. (Note: AERA stands for American Educational Research Association that has also one of the large members in the nation and the world. ATE stands for Association for Teacher Educators; NAME stands for National Association for Multicultural Education). Third, this book can be purchased as reading text materials by college students in teacher education and training programs. There are many federal and state funding projects that have the budget for purchasing training materials. In addition, school districts can purchase the book for their in-service teachers. Through the grant programs, we also have the contact with the key personnel in the four target school districts (e.g., ESOL curriculum program coordinators) and we can encourage them to market the book through our good relation; the ESOL teachers and school personnel can recommend the books for further adoption in other K-12 classroom teachers since South Carolina has the highest increase in the ELL population and every teacher need to know how to teach ELLs"-- Provided by publisher.
Keywords: English language -- China.; English language -- Study and teaching -- China.; English language -- Study and teaching -- Chinese speakers.; Language Arts & Disciplines -- Study & Teaching.; Language teaching theory and methods.; Language teaching and learning.; elektronické knihy; electronic books